"I throw the last punch": How students cope with school violence - Pacheco-Salazar, Berenice; López-Yáñez, Julián (Revista Complutense de Educación, 2018)
Presentation of the results of qualitatively designed descriptive research aimed at identifying the strategies that students use in response to school violence. The study, which was conducted in primary schools in the Dominican Republic, is based on a sample of 604 fifth— to eighth-grade students. Three information-gathering techniques were used: playful-creative workshops, focus groups and non-participant observation, which involved spending a four-month immersion period in each school. The results of this research highlight that the most common way in which the students respond to a violent incident at school is to defend themselves by using violence, i.e. “throwing the last punch.” To a lesser extent, they may also seek help from adults or report the incident to the school authorities. The findings and conclusions are relevant for the design and implementation of programs aimed to prevent and eradicate school violence.